Pathways to Racial Equity in Higher Education: Modeling the Antecedents of State Affirmative Action Bans. (October 2019) - Baker, Dominique J.
Eight states currently have bans on affirmative action, yet little research has focused on the characteristics of states that predict ban adoption. To begin filling this gap in the literature, I conduct discrete-time survival analysis on an aggregated data set of 47 states from 1995 to 2012 to investigate the extent to which various characteristics of a state predict its likelihood of adopting a statewide affirmative action ban. Results show that scarcity of access to state public flagship institutions and policy diffusion are associated with ban adoption. Aligning with the racial threat literature, the findings suggest that these bans are associated with concerns about the scarcity of access to selective higher education institutions (operationalized as state public flagships) for White students.